Applying amplification refractory mutation system technique to detecting cell-free fetal DNA for single-gene disorders purpose - Tan, Yu; Jian, Hui; Zhang, Ranran; Wang, Jing; Zhou, Cong; Xiao, Yuanyuan; Liang, Weibo; Wang, Li (Frontiers in Genetics, 2023)
Non-invasive prenatal diagnosis for single-gene disorders (NIPD) is still in development and deserves further study. The advent of next-generation sequencing technology significantly improved the detection of multiple mutations for non-invasive prenatal diagnosis for single-gene disorder purposes. However, bespoke amplicon-based NGS assays are costly. In this study, we developed a new strategy for non-invasive prenatal screening for single-gene disorders based on a capillary electrophoresis (CE) platform using an amplification refractory mutation system (ARMS)-PCR technique. Allele-specific primers for several disease-correlated mutations were designed, and subsequently, sensitivity and specificity assays were conducted. Assays on simulated two-person DNA mixtures showed that three primers targeting the mutant allele could detect minor DNA components in 1:500 mixtures. All primers showed positive results at 0.01 ng of the template DNA. Cell-free fetal DNA was extracted from a pregnant woman’s peripheral blood for the detection of paternally inherited mutations. Our results showed that one primer successfully amplified the mutant allele of fetal DNA in maternal plasma, which was confirmed by genotyping the genomic DNA extracted from amniotic fluid. This study suggested that the ARMS-PCR technique, a fast and cost-effective method, might be a promising method used to target de novo or paternally inherited pathogenic mutations in maternal plasma.